Risk Factors for South Korea Male Intimate Partner Violence (IPV) Victims Only, and Victim-Offenders - Kim, Chunrye; Won, Haemi
Intimate partner violence (IPV) is a serious social issue in South Korea. However, many scholars and policymakers in South Korea tend to focus disproportionately on men as IPV perpetrators, rather than acknowledging their role as victims or both victims and offenders simultaneously. To develop the treatment and intervention strategies tailored to IPV associated with each group. Using the data from the Violence Against Women, Focused on Intimate Partner Violence study examined (1) the prevalence of IPV perpetration, victimization, and both perpetration and victimization; (2) how the prevalence rate varies depending on the nature of violence (i.e., violent vs. non-violent); and (3) the factors associated with each group, using multi-nominal analyses. We found that each type of violence (i.e., physical, sexual, emotional, and controlling behaviors) was statistically different from the others when measuring IPV perpetration only, victimization only, and both IPV perpetration and victimization. In both violent and non-violent types of IPV, Korean men who had experience only IPV perpetration, as well as those who had experienced both IPV perpetration and victimization, tended to share similar risk factors, such as witnessing parental abuse and having lower levels of self-control , when compared to the IPV victimization-only group. The IPV victimization-only group exhibited a unique risk factor. Results confirm the previous literature's findings that some similarities exist among Korean IPV offenders, IPV victims, and IPV victim-offenders, but there are distinct characteristics among them as well.
Keywords: IPV perpetration; South Korean men